1984
DOI: 10.1111/j.1600-0722.1984.tb00885.x
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of maxillary sinus, palate and maxillary gingiva: occurrence of jaw destruction

Abstract: – A comparison was made between the frequency of alveolar bone‐palate destruction caused by carcinomas originating in the maxillary sinus (31 patients), palate (15) and maxillary gingiva (9). Radiographic examination included conventional sinus projections, supplemented with hypocycloid tomography (47), computed tomography (28) and orthopantomography (11). Almost every second tumor presenting with alveolar bone involvement appeared to be a maxillary sinus cancer. Gingival and palatal cancers also caused frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
1990
1990

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…A variety of reports has appeared in the literature which described entities that presented with clinical and radiographic features of inflammatory periodontal disease, but which did not respond adequately to conventional periodontal therapy, or were inconsistent with the general periodontal status of the patient. Histiocytosis X has presented with the clinical features of localized juvenile Periodontitis, as well as with features of both generalized and localized Periodontitis.13*14 Varying degrees of osseous destruction have also been reported to occur with malignant lymphoma of the oral cavity.15 Larheim et al 16 presented 31 cases involving carcinoma of the maxillary sinus, palate, and/or gingiva, and found that each of these was frequently associated with osseous destruction. A review of metastatic carcinomas which have appeared at mandibular sites has been reported by Hashimoto et al,17 and a case of metastatic hepatocellular gingival carcinoma with localized osseous destruction was presented by Morishita and Fukuda.18 Significantly, many of the foregoing cases occurred in patients with at least moderate periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of reports has appeared in the literature which described entities that presented with clinical and radiographic features of inflammatory periodontal disease, but which did not respond adequately to conventional periodontal therapy, or were inconsistent with the general periodontal status of the patient. Histiocytosis X has presented with the clinical features of localized juvenile Periodontitis, as well as with features of both generalized and localized Periodontitis.13*14 Varying degrees of osseous destruction have also been reported to occur with malignant lymphoma of the oral cavity.15 Larheim et al 16 presented 31 cases involving carcinoma of the maxillary sinus, palate, and/or gingiva, and found that each of these was frequently associated with osseous destruction. A review of metastatic carcinomas which have appeared at mandibular sites has been reported by Hashimoto et al,17 and a case of metastatic hepatocellular gingival carcinoma with localized osseous destruction was presented by Morishita and Fukuda.18 Significantly, many of the foregoing cases occurred in patients with at least moderate periodontal disease.…”
Section: Discussionmentioning
confidence: 99%